Some New Explicit Values of Quotients of Theta-Function ϕ(q) and Applications to Ramanujan's Continued Fractions. (7th March 2013) - Saikia, Nipen
Abstract : We find some new explicit values of the parameter h k, n for positive real numbers k and n involving Ramanujan's theta-function ϕ ( q ) and give some applications of these new values for the explicit evaluations of Ramanujan's continued fractions. In the process, we also establish two new identities for ϕ ( q ) by using modular equations.